الجزائر الوسيطة فى نظر المدرسة الكولونيالية - جغوبي,الأخضر; ببوخة,فرحات (University of Eloued جامعة الوادي, 2024)
Many French researchers and historians dealt with the history of the region in all its periods and aspects, as colonial France sought to write the history of Algeria through the writings of military historians, specialized historians, various committees and associations, and translated and published local and Arab manuscripts, which reflects a complex interplay between scientific interest, preparing the ground, and providing the field data necessary for the success of the region. The colonial project, they collected important scientific knowledge about the Central Maghreb (Algeria) and published it in the form of books and writings that contributed to revealing the history and characteristics of Algerian society, although from a biased, racist perspective that aimed to justify colonial rule and undermine the history and civilization of Algeria and confirm the superiority of French civilization. Charles Andre Julien is an example of these writings. His book “The History of North Africa,” which covers its history from ancient times until the modern era, is considered one of the important works that deals with the history of the region. In the book, Julien provides an accurate analysis of the historical events and developments in the region, relying on a wide range of sources. Historical. Through this research note, we attempt to clarify the relationship between French colonialism and the historical writings that Western historians (Orientalists) tried to promote about the Maghreb in general and the Middle Maghreb in particular, and the means they adopted in doing so.
شارل اندري جوليان ـــ أمنوذجا ــ
Keywords: المؤرخين العسكريين; المغرب الاو; س; Central Morocco; researchers and historians; military historians; various associations; French civilization.